Who are CHWs? An ethnographic study of the multiple identities of community health workers in three rural Districts in Tanzania - Mohamed Yunus Rafiq; Hannah Wheatley; Hildegalda P. Mushi; Colin Baynes (BMC, 2019)
Abstract Background Numerous studies have examined the role of community health workers (CHWs) in improving the delivery of health services and accelerating progress towards national and international development goals. A limited but growing body of studies have also explored the interactions between CHWs' personal, communal and professional identities and the implications of these for their profession. CHWs possess multiple, overlapping roles and identities, which makes them effective primary health care providers when properly supported with adequate resources, but it also limits their ability to implement interventions that only target certain members of their community, follow standard business working days and hours. In some situations, it even prevents them from performing certain duties when it comes to sensitive topics such as family planning. Methods To understand the multiple identities of CHWs, a mixture of qualitative and ethnographic methods was utilized, such as participant observation, open-ended and semi-structured interviews, and focus group discussions with CHWs, their supervisors, and their clients. The observation period began in October 2013 and ended in June 2014. This study was based on implementation research conducted by the Connect Project in Rufiji, Ulanga and Kilombero Districts in Tanzania and aimed to understand the role of CHWs in the provision of maternal and child health services in rural areas. Results To our knowledge, this was the first study that employed an ethnographic approach to examine the relationship between personal, communal and professional identities, and its implications for CHWs' work in Tanzania. Our findings suggest that it is difficult to distinguish between personal and professional identities among CHWs in rural areas. Important aspects of CHW services such as personalization, access, and equity of health services were influenced by CHWs' position as local agents. However, the study also found that their personal identity sometimes inhibited CHWs in speaking about issues related to family planning and sexual health. Being local, CHWs were viewed according to the social norms of the area that consider the gender and age of each worker, which tended to constrain their work in family planning and other areas. Furthermore, the communities welcomed and valued CHWs when they had curative medicines; however, when medical stocks were delayed, the community viewed the CHWs with suspicion and disinterest. Community members who received curative services from CHWs also tended to become more receptive to their preventative health care work. Conclusion Although CHWs' multiple roles constrained certain aspects of their work in line with prevalent social norms, overall, the multiple roles they fulfilled had a positive effect by keeping CHWs embedded in their community and earned them trust from community members, which enhanced their ability to provide personalized, equitable and relevant services. However, CHWs needed a support system that included functional supply chains, supervision, and community support to help them retain their role as health care providers and enabled them to provide curative, preventative, and referral services.